A back-to-back converter system for aerospace applications - Hao Zhe, Chua (2018)
In the aerospace industry, reducing the weight of aerospace applications has been an important factor on their performance, such as speed and rate of climb. The effect of weight is not proportionate to aerospace’s performance. The greater the weight, the lower the performance. In the industrial and power systems applications, Back-to-Back converter has been a widely used topology for bidirectional AC-AC converters. The boosted DC-link voltage in the converter allows machine to increase its output power over the rated power. It also has the ability of rapid control of power flow in the converter and provide power balance between both ends of the converter. The ability to control the power flow allows the DC-link voltage to be regulated, which results in size reduction of the DC-link capacitor without affecting its performance. Moreover, capacitors are generally bulky and costly. Hence, the reduction in size for capacitors would be favourable in aerospace applications if a Back-to-Back converter system was to be implemented. This report studies the Back-to-Back converter topology and conversion. It covers the converters being used and the control circuit to control the power flow within them. Simulation software, such as PSIM, is introduced for circuit design and simulation. The report consists of 2 main parts. Firstly, the working principles on different types of converters and other subsystems. Secondly, the design of the converter, types of simulation and the results.